The Effectiveness of Self-Care Management Education on Increasing Self-Efficacy in Pulmonary Tuberculosis Patients - Supriyadi Supriyadi; Dewi nur Sukma Purqoti; Irwan Budiana; Wanti Wanti (Journal of Tropical Diseases and Health Science, 2026)
Pulmonary TB is a chronic disease that requires long-term treatment with medication and causes physical impacts. Treatment adherence is influenced by the level of knowledge, family support, self-management, self-stigma, and self-efficacy. Self-efficacy is essential during treatment to increase self-confidence in managing and caring for oneself. One effort to increase self-efficacy is by providing adequate information regarding self-care methods through Management Self-Care education. The purpose of this study was to analyze the effect of management self-care education on self-efficacy in pulmonary TB patients. The research design used a pre-experimental approach with a one-group pre-post test approach. The sample consisted of 16 respondents selected using a purposive sampling technique. The research instrument used a questionnaire Guide for constructing self-efficacy scale (GFCSES). The average pretest score was categorized as moderate (35.25) with the lowest score of 31, the highest score of 42, and a standard deviation of 2.97. Meanwhile, the average posttest score was categorized as high (47.06), with the lowest score being 45, the highest score being 50, and a standard deviation of 1.73. Analysis using a paired sample t-test showed a p-value of 0.00 (<α 0.05). This indicates that self-care management has an effect on self-efficacy in pulmonary TB patients in the Gunung Sari Community Health Center work area in 2024. This research is expected to provide benefits and can be further developed as a source of knowledge for readers in general.